Interactions of Drosophila Ultrabithorax regulatory regions with native and foreign promoters. - Casares, F.; Bender, W.; Merriam, J.; Sanchez-Herrero, E. (Genetics, 1997)
The Ultrabithorax (Ubx) gene of the Drosophila bithorax complex is required to specify parasegments 5 and 6. Two P-element "enhancer traps" have been recovered within the locus that contain the bacterial lacZ gene under the control of the P-element promoter. The P insertion that is closer to the Ubx promoter expresses lacZ in a pattern similar to that of the normal Ubx gene, but also in parasegment 4 during embryonic development. Two deletions have been recovered that remove the normal Ubx promoter plus several kilobases on either side, but retain the lacZ reporter gene. The lacZ patterns from the deletion derivatives closely match the normal pattern of Ubx expression in late embryos and imaginal discs. The lacZ genes in the deletion derivatives are also negatively regulated by Ubx and activated in trans by Contrabithorax mutations, again like the normal Ubx gene. Thus, the deleted regions, including several kilobases around the Ubx promoter, are not required for long range interactions with Ubx regulatory regions. The deletion derivatives also stimulate transvection, a pairing-dependent interaction with the Ubx promoter on the homologous chromosome.